Relationship between the MDS-UPDRS and Quality of Life: A large multicenter study of 3206 patients. (July 2018) - Skorvanek, Matej; Martinez-Martin, Pablo; Kovacs, Norbert; Zezula, Ivan; Rodriguez-Violante, Mayela; Corvol, Jean-Christophe; Taba, Pille; Seppi, Klaus; Levin, Oleg; Schrag, Anette; Aviles-Olmos, Iciar; Alvarez-Sanchez, Mario; et al.
Abstract: Background: The relationship between Health-Related Quality of Life (HRQoL) and MDS-UPDRS has not been fully studied so far. The aim of this study was to evaluate the relationship between all MDS-UPDRS components and HRQoL in a representative international cohort of PD patients. Methods: We collected demographic and disease-related data as well as MDS-UPDRS and PDQ8 scales. Data were analyzed using correlations between PDQ8 and all MDS-UPDRS items, subsequently two hierarchical multiple regressions were performed, first between the scores of the MDS-UPDRS Parts and PDQ8 and second between individual items from those Parts demonstrating significant relationship to PDQ8 scores in the first regression. LASSO regression analyses were performed to evaluate the relationship between PDQ8 and all individual MDS-UPDRS items. Results: A total of 3206 PD patients were included in the study. In the first regression analysis, PDQ8 was significantly related to MDS-UPDRS parts I and II, but not to III and IV. In the second regression model, significant contributions to PDQ8 were found for Part I items Fatigue, Pain, Depressed mood, Apathy; and Part II items Dressing, Doing hobbies, Freezing, Speech and Tremor. In the LASSO analysis, six Part I, seven Part II, three Part III and one Part IV items contributed to PDQ8 scores. The five items most significantly related to the model were Depressed mood, Dressing, Apathy, Pain and Fatigue. Conclusions: This is so far the largest study related to HRQoL issues in PD. Restrictions in activities of daily living and non-motor symptoms significantly contribute to HRQoL in PD. Highlights: This is the largest study related to Quality of Life (QoL) in PD so far. QoL is related especially to MDS-UPDRS Part II (ADLs) and Part I (NMS). Four out of five most important independent contributors were non-motor items.